HOW ARE BRANDS AFFECTED BY THE USE OF FOOD ECO-LABELS? REVISITING BRAND IMAGE AND PURCHASE INTENTIONS - Langaro, D.; Brântuas, M.P. (EMAC 2023 Regional Conference, 2023)
- The impacts of climate change on the planet have brought to light green concerns and needed initiatives to address environmental problems. Eco-labels provide information related to the environmental performance of products/services, enabling consumers to easier identify greener product alternatives. This paper explores whether eco-labels are capable of generating green behaviours amongst consumers as a way to reach sustainable consumption. Design/methodology/approach - The research employs a survey-based method to test a set of theoretically anchored hypotheses. It uses simple and multiple linear regression models by OLS (Ordinary Least Squares) and tests variable moderation through PROCESS analysis to undertake an empirical study. The research object of this study is the answers of 392 consumers. Findings - The results have proven that eco-labels can drive purchase intentions of green products since they add positive associations to brands, favourably influencing the brand image. Additionally, the outcomes revealed that familiarity with the eco-label moderates this relationship, as higher levels of eco-label familiarity generated higher levels of brand image. Hence, this study suggests that companies should promote their green initiatives – such as eco-labels – to foster consumers’ awareness and drive sustainable consumption. Originality/value - Most studies analyse the factors influencing eco-labels capacity to generate green behaviours. However, none has studied the influence of eco-labels on brands’ image and whether brands can benefit from the presence of these certifications. This study builds into the concept of Brand Image presented within the Customer-Based Brand Equity (CBBE) model by Kevin Keller (1993).